Improving Trust in Research: Supporting Claims with Evidence - Wright Daniel B. (De Gruyter, 2020)
Trust in science is important, and Open Education Studies aims to publish trusted research. Two issues are addressed here: access to the data on which the research is based and how these data are analyzed. Some guidelines from other entities are discussed. As a new journal our guidelines should be influenced by the opinions of readers and authors, and as such we welcome discussion of how to ensure trust in the research OES publishes.